EEG signal recognition for brain word interface using wavelet decomposition - Hema, Chengalvarayan Radhakrishnamurthy; Leong, Shi Wei; Erdy Sulino, Mohd Muslim Tan (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/